KERONCONG MUSIC REDUCES POSTOPERATIVE PAIN IN CRITICAL CARE UNIT - RAIMONDA AMAYU IDA VITANI (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2016)
Background: Pain that has been experienced by patients in intensive care can lead them into worse condition. The efforts relieving the pain have been done a lot. One of them is to use music therapy. Nevertheless, the researcher has not found the the research of keroncong music therapy as original Indonesian classical traditional music for pain. Purpose: The aims of this study was to know the effect of keroncong music for pain level of the postoperative patients in intensive care. Method: This research used quasy experimental with pre-post nonequivalent control group design on 32 postoperative patients in critical care rooms. Keroncong music therapy has been implemented to the second day postoperative patients, it has been given twice a day and each implementation the patients listened keroncong music for 20 minutes. The pain level was measured using Visual Analogue Scale (VAS). Result: Postoperative pain level in intervention group (22,94 ± 14,63) significantly decreased than control group (2,06 ± 21,90) with p = 0,003, with a difference of mean 20.88 mm decrease in pain.Conclusion: Keroncong music therapy had effect on the decreasing of pain level of postoperative patients. Keroncong music therapy can be recommended to be independent complementary nursing intervention to decrease the pain level of postoperative patients in intensive care unit.